Do what you want : the story of Bad Religion - Ruland, Jim (Hachette Books, 2020)
"The all-access autobiography of Bad Religion, a Southern Californian institution and one of the most influential and long-standing punk rock bands of all time In 1980, punk was declared dead in New York, done-for in London, banned in Hollywood. And yet just under the radar, the punk rock virus had continued to spread, slowly inching its way through the breezy beach towns of Southern California and into the edgier interior of East LA. Embraced by the skaters and surfers, and hated by just about everyone else, the LA punk scene ebbed and flowed in the early '80s, each wave ushering in an increasingly aggressive cycle of reformers. It was within this hotbed of deliberate dissonance, lyrical intensity, and untapped teen angst that Bad Religion was born. In Do What You Want, the legendary band tells us the story of their success in their own words, from jamming out in a 'hell hole-ish' garage in the 1980s to headlining sold-out festivals like Coachella, Lollapalooza, Riot Fest, and more. Our principal storytellers are the four voices that define Bad Religion: Greg Gaffin, a Wisconsin kid who sang in the choir and became a punk rock icon while he was still a teenager; Brett Gurewitz, a high school dropout who later founded the infamous indie punk label Epitaph Records, eventually expanding its net and cache to sign legends like Tom Waits and Merle Haggard; Jay Bentley, a surfer and skater who gained recognition as much for his bass skills as for his outlandish onstage antics; and Brian Baker, a hardcore guitarist who joined the band in 1994 and brings a fresh perspective as an intimate outsider. Do What You Want also features additional interviews from former band members and fellow rock stars like Fat Mike (NOFX), Keith Morris (Black Flag and the Circle Jerks), and many more. With hit after hit dominating the radio waves, Bad Religion also paved the way for the punk rock explosion of the 1990s, opening the door for bands like Blink-182, Green Day, and NOFX to reach a wider audience. They showed the world what punk could be, and they continue to spread their message one song, one show, one tour at a time--with no signs of stopping. Do What You Want isn't a book about a band that's sitting on the sofa and rewriting their history. Bad Religion is at the top of their game, one of the last bands standing with legit punk roots, mainstream success, and widespread appeal"--